Investigating Antibiotic Resistance Genes in Marketed Ready‐to‐Eat Small Crickets (Acheta domesticus). Issue 11 (10th October 2019) - Roncolini, Andrea; Cardinali, Federica; Aquilanti, Lucia; Milanović, Vesna; Garofalo, Cristiana; Sabbatini, Riccardo; Abaker, Mahasin Salih Suliman; Pandolfi, Matteo; Pasquini, Marina; Tavoletti, Stefano; Clementi, Francesca; Osimani, Andrea
Abstract : Abstract: The present investigation was aimed at evaluating the occurrence of transferable genes conferring resistance to tetracyclines, macrolide‐lincosamide‐streptogramin B (MLSB ), vancomycin, beta‐lactams, and aminoglycosides in 32 samples from eight batches of ready‐to‐eat crickets ( Acheta domesticus ) commercialized by four European Union producers (two batches per producer). Bacterial DNA extracted directly from the insects was subjected to optimized polymerase chain reaction (PCR) and nested‐PCR assays for the qualitative detection of 12 selected antibiotic resistance (AR) genes. Microbial enumeration demonstrated high counts of spore‐forming bacteria and total mesophilic aerobes. Statistical analyses revealed significant differences between different producers and insect batches. Regarding AR genes, a high prevalence of genes conferring resistance to tetracycline [ tet (M), tet (O), tet (K), tet (S)] was observed, together with the presence of genes conferring resistance to erythromycin [ erm (B), erm (C)], beta‐lactams ( blaZ and mecA ), and aminoglycosides [ aac(6') ‐ Ie aph(2")‐Ia ]. We performed a principal component analysis based on the AR gene frequencies that differentiated samples of batch 1 from those of batch 2. This analysis provided evidence for a difference between the producer from France and all the other producers among the batch 1 samples. Practical application: Overall, an intrabatch variation was seen in the transferable resistances among different producers. This evidence, coupled with the observed differences in the viable counts, suggests a low standardization of the production processes. Hence, a prudent use of antimicrobials during the rearing of insects destined for human consumption is strongly recommended, as well as a need for a full standardization of production technologies.